STRATEGI PENGGUNAAN MEDIA DIGITAL DALAM PROMOSI KERAJINAN PARANG SUMBAWA (STUDI KASUS KOMUNITAS PANDAI BESI DESA LESENG, KECAMATAN MOYO HULU) - Fahrunnisa; Qonitat, Izzatul (Jurnal TAMBORA, 2020)
In the digital era, it is important for business units to rely on the internet to be able tosurvive and expand into a wider market. In its use, digital mediamust be supported by a good strategy, so that the product can be competitive.Leseng Village is a center for machete craftsmen in Sumbawa who also make use of itdigital media for marketing. The media they use are Facebook andWhatsApp, but in marketing it has not been maximized in digital marketing. This matteras evidenced by the absence of an official community account / blog of machete crafter, howeverjust use a personal account. So based on these problems,The research was conducted aimed at examining the extent of the craftsmenmaximize the use of digital media in supporting the promotion of machetesSumbawa.This research uses qualitative methods with a case study approach. Researchconducted in Leseng Village, MoyoHulu District with a research period ofSeptember-March 2020. The informant from the study was a machete craftsmanusing digital media in marketing its products. Discussion analysisusing the theory of Tom Duchan in marketing communications.The results of the research in the village of Leseng contained 31 groups of machete craftsmen, and thoseonly 3 groups of machete craftsmen used digital media. Usage strategythe media by machete craftsmen when analyzed using theory has not appliedthe concept. In theory there are 4 stages, the first is the target of the media, not the machete craftsmendetermine specific target consumers. The second goal of the media, media designusing Facebook and WhatsApp but using their respective personal accounts. The third strategy, the strategy they are doing is just spreading the message togroups / pages on Facebook. The fourth is media scheduling, not machete craftsmenhave the best time to do promotions.